2015
DOI: 10.1111/jicd.12202
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of sinusitis of odontogenic origin

Abstract: Sinusitis of odontogenic origin, which is frequently encountered in routine otolaryngological and dental clinical practice, has been described as a reactive maxillary inflammation secondary to maxillary tooth infection or trauma to an odontogenic disease of maxillary bone, dental extractions, implant placement, or endodontic treatment impairing the integrity of the Schneiderian membrane. The aim of the present review was to investigate and discuss the most recent pathophysiological findings, predisposing odont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 80 publications
0
40
0
2
Order By: Relevance
“…Bauer showed that inflammation and infection from tooth roots could spread through maxillary alveolar bone and sinus mucosa, thereby causing sinus inflammation and infection . Various odontogenic pathologies can cause ODS, including pulpitis, periapical lesions (cysts, abscesses, granulomas), periodontitis, oroantral fistula (OAF), or dental treatment‐related sinus foreign bodies . Large series and meta‐analyses have shown that the main dental etiologies of ODS are extraction‐related OAFs, periapical, and periodontal disease …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bauer showed that inflammation and infection from tooth roots could spread through maxillary alveolar bone and sinus mucosa, thereby causing sinus inflammation and infection . Various odontogenic pathologies can cause ODS, including pulpitis, periapical lesions (cysts, abscesses, granulomas), periodontitis, oroantral fistula (OAF), or dental treatment‐related sinus foreign bodies . Large series and meta‐analyses have shown that the main dental etiologies of ODS are extraction‐related OAFs, periapical, and periodontal disease …”
Section: Introductionmentioning
confidence: 99%
“…8 Various odontogenic pathologies can cause ODS, including pulpitis, periapical lesions (cysts, abscesses, granulomas), periodontitis, oroantral fistula (OAF), or dental treatment-related sinus foreign bodies. 9,10 Large series and meta-analyses have shown that the main dental etiologies of ODS are extraction-related OAFs, periapical, and periodontal disease. [11][12][13][14] ODS is diagnosed in a fashion similar to other forms of sinusitis: history to detect sinusitis symptoms, nasal endoscopy to assess for inflammation or infection, and computed tomography (CT) imaging to assess sinusitis extent but also maxillary odontogenic pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the etiology, various odontogenic pathologies can cause OMS, including pulpitis, periapical lesions, periodontitis, oroantral fistulas, or foreign bodies in the sinus related to dental treatment . However, the presence of periapical lesions is significantly associated with the thickening of the maxillary sinus mucosa and to OMS .…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, endodontic treatments are considered one of the most important risky procedures for maxillary pathology: in fact, during this procedure, the endodontic material, which contains zinc oxide-eugenol, facilitates the growth of Aspergillus fumigatus , paralyses the mucosa-cilia and induces soft-tissue oedema 1 13. Another common consequence of teeth inflammatory process is the formation of odontogenic cyst, whose origin is still unclear:2 14 15 this cyst could be another odontogenic focus from which an odontogenic rhinosinusitis may occur.…”
Section: Discussionmentioning
confidence: 99%
“…They are generally regarded as maxillary-only sinusitis arising from dental pathology, featuring unilateral nasal obstruction and/or purulent discharge, pain or pressure on the maxillary area and cacosmia 1. Patients may also have episodes of gravel-like discharge from their nose 2…”
Section: Introductionmentioning
confidence: 99%